2015
DOI: 10.1111/ssm.12145
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Science Standards: A National Mixed‐Methods Study on Teacher Readiness

Abstract: Next Generation Science Standards (NGSS) science and engineering practices are ways of eliciting the reasoning and applying foundational ideas in science. As research has revealed barriers to states and schools adopting the NGSS, this mixed-methods study attempts to identify characteristics of professional development (PD) that will support NGSS adoption and to improve teacher readiness. In-service science teachers from across the nation were targeted for the survey and responses represented 38 states. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Providing professional development for teachers is essential and several studies have proved so (Colwell et. al., 2014;Haag & Megowan, 2015: Micheal, et al, 2016Tondeur, et al, 2016;Sibert, & Rieg, 2016). However, identifying, the right professional development is critical.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Providing professional development for teachers is essential and several studies have proved so (Colwell et. al., 2014;Haag & Megowan, 2015: Micheal, et al, 2016Tondeur, et al, 2016;Sibert, & Rieg, 2016). However, identifying, the right professional development is critical.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The NGSS expect teachers to shift classroom pedagogy largely to an inquiry and project based approach to learning. Haag and Megowan (2015) found that teachers trained in the use of modeling instruction, one type of inquiry-based learning, expressed greater self-assessed readiness to implement the NGSS than their peers who had not received training in modeling instruction.…”
Section: Description Of the Theoretical Frameworkmentioning
confidence: 95%
“…Resistance to the implementation of the NGSS, both in terms of content and pedagogy exists (Haag & Megowan, 2015). Simply mandating a curriculum change will not in and of itself change the curriculum, unless steps are taken to help all stakeholders and actors to understand the change (Priestley, 2011).…”
Section: Locus Of Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that this approach should facilitate teaching, it possesses certain challenges for tutors at the initial stage of implementation (Haag & Megowan, 2015). A recent study reveals that the teachers require more time to learn utilizing the modern technologies in classroom practices (Kennedy, Rhoads, & Leu, 2016).…”
Section: Importance Of the Problemmentioning
confidence: 99%